Novel PTPRQ variants associated with hearing loss in a Chinese family PTPRQ variants in Chinese hearing loss - Hou, Yuan; Shi, Yuanzhen; Liu, Longyan; Duan, Shihong (Frontiers in Genetics, 2024)
Hearing loss is one of the most prevalent congenital sensory disorders. Over 50% of congenital hearing loss cases are attributed to genetic factors. The PTPRQ gene encodes the protein tyrosine phosphatase receptor Q, which plays an important role in maintaining the structure and function of the stereocilia of hair cells. Variants in the PTPRQ gene have been implicated in hereditary sensorineural hearing loss. Utilizing next-generation sequencing technology, we identified novel compound heterozygous variants (c.977G>A:p.W326X and c.6742C>T:p.Q2248X) in the PTPRQ gene within a Chinese national lineage, marking the first association of these variants with hereditary sensorineural hearing loss. Our findings further emphasize the critical role of PTPRQ in auditory function and contribute to a more comprehensive understanding of PTPRQ-associated hearing loss mechanisms, aiding in clinical management and genetic counseling.